FinTech and financial inclusion: unpacking the links to inequality - Figueira, Catarina; Subramanian, Lakshmy (Financial Research and Trading Laboratory (FRTL), 2025)
This investigation analyses how financial inclusion, dimensions of inequality and financial technology (FinTech), are related across 113 countries using data from the 2011–2021 Global Findex survey. The study finds both direct and indirect associations between the different constructs employing structural equation modelling methodologies. The primary findings reveal that FinTech simultaneously worsens income inequality while narrowing gender gaps through enhanced financial inclusion. Additionally, these technologies promote broader financial participation among excluded sections of the population. Greater financial inclusion lowers both economic and gender-based inequalities. The research also explains that effective regulation, educational opportunities, and availability of credit can contribute to more equitable outcomes through financial inclusion. These findings add to emerging scholarships on how financial technological innovation and robust financial inclusion initiatives can improve resource allocation and promote more inclusive economic development globally. This represents the first comprehensive examination of multiple inequality types and their complex relationships within this framework. The study provides preliminary evidence of the varying distributional implications of technology-based finance and financial inclusion on several types of inequalities.
Keywords: FinTech; Financial inclusion; Income Inequality; Gender Inequality Structural Equation Modelling